Exploring Irrigable Dams Schemes and Water Quality for Vegetable Cultivation in Wa West District, Upper West Region-Ghana - Fagariba, Clifford James; Sumani, John Bosco Baguri (European Scientific Journal, ESJ, 2026)
Water is vital for existence and is universally acknowledged as the paramount natural resource. Water consumption is essential for individuals and various activities in both the formal and informal sectors. This study sought to assess irrigable dam schemes and water quality for vegetable cultivation in the Wa West District, Upper West Region of Ghana. Simple random sampling was employed to select 296 vegetable farmers in the study area. Additionally, a key expert interview was employed to extract information from 50 prominent experts across various government agencies and stakeholders. The research utilized a weighted average index (WAI) to evaluate the viewpoints of the key informants. The study additionally utilized spectrophotometric analysis to examine the water resources of irrigable dams within the research area. The evaluated physico-chemical parameters of water quality revealed that nitrogen, fluoride, potassium, and phosphorus concentrations in the dams surpassed the WHO water quality standards. The study findings revealed that nearly 96% of respondents in the study area obtained their livelihoods directly or indirectly from the dam’s water resources. The study concluded that augmenting the capabilities of farmers and households in strategies to mitigate dam pollution would substantially enhance dam protection. It is advisable to effectively disseminate extension programs to furnish pertinent information on irrigable dam systems, thereby improving farmers’ adoption of irrigation technology. Authorities must consistently enforce and advocate for the proper utilization of fertilizers on irrigable farms. This pattern will alleviate the potential adverse impacts of nitrogen, phosphate, potassium, and other contaminants on water, resulting in a deterioration of water and agricultural quality. Collaborative partnerships among essential stakeholders, including community members, will enhance the efficiency and conservation of water resources in the Wa West District and adjacent regions.